The Dynamics of Transcultural Insight in Jhumpa Lahiri’s Literary Universe - Adriana Elena Stoican (Baltic Journal of English Language, Literature and Culture)
Blending literary and cultural studies, the essay discusses the manners in which Jhumpa Lahiri’s literary universe constructs a gradual unfolding of a layered transcultural vision.